2021
DOI: 10.1021/acs.analchem.1c02914
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Enrichment of Submicron Particles within a Spinning Droplet Driven by a Unidirectional Acoustic Transducer

Abstract: Efficient and rapid particle enrichment at the submicron scale is essential for research in biomedicine and biochemistry. Here, we demonstrate an acoustofluidic method for submicron particle enrichment within a spinning droplet driven by a unidirectional transducer. The unidirectional transducer generates intense sound energy with relatively low attenuation. Droplets placed offset in the wave propagation path on a polydimethylsiloxane film undergo strong pressure gradients, deforming into an ellipsoid shape an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Previous studies showed that these forces produce observable spiral flow patterns around the spin axis which are expected. 57,[62][63][64] In this work, a spinning liquid marble is achieved by placing it at the centre of a spinning cup where the rotational speeds of both the liquid marble and cup are synchronous. When a liquid marble spins from rest, it flattens slightly due to centrifugal forces.…”
Section: Spinning Of a Liquid Marblementioning
confidence: 99%
“…Previous studies showed that these forces produce observable spiral flow patterns around the spin axis which are expected. 57,[62][63][64] In this work, a spinning liquid marble is achieved by placing it at the centre of a spinning cup where the rotational speeds of both the liquid marble and cup are synchronous. When a liquid marble spins from rest, it flattens slightly due to centrifugal forces.…”
Section: Spinning Of a Liquid Marblementioning
confidence: 99%
“…Particle concentration at the microscale is of great significance in various biomedical and biochemical applications, including micro/nano-assembly [ 1 , 2 ], tissue engineering [ 3 , 4 ], and biomedical detection [ 5 ]. The concentration process is usually a crucial sample preparation step in related biomedical applications such as biosensors [ 6 ], and 3D cell culture [ 7 ]. Microparticle concentration realized by efficient fluidic methods has become an important research area.…”
Section: Introductionmentioning
confidence: 99%
“…With acoustic wave actuation, precise and efficient particle manipulation from nanometer to micron scale can be achieved based on the induced acoustic radiation force and acoustic streaming [ 17 ]. Existing methods for acoustic concentration mainly include surface acoustic wave (SAW) [ 6 , 18 , 19 ], and flexural wave [ 12 , 20 , 21 ] vary with the used transducer. According to the analytical equation f = c / λ , SAW with the required resonant frequency f and specific type can be generated by fabricating interdigital electrodes (IDTs) with specific finger width on the substrate such as 128° YX Lithium Niobate [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particles contactless manipulation such as concentration, aggregation and separation in microfluidics is previously considered to be the result of the combined action of the two forces: acoustic radiation force (F Gov kov ), acoustic streaming drag force (F D ) or tea leaf effect [1][2][3]. However, it is unlikely to be due to the radiation force because similar phenomena can be observed without acoustic field, which can reference the study of Yeo et al [4].…”
Section: Introductionmentioning
confidence: 99%